2022
DOI: 10.12968/bjom.2022.30.8.426
|View full text |Cite
|
Sign up to set email alerts
|

Research skills in practice

Abstract: Kelda Folliard and Ruth Sanders discuss facilitating the conceptual leap for student midwives towards embedding evidence-based practice and research in midwifery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In its ‘International Code of Ethics for Midwives’, the ICM describes that midwives use up-to-date data and professional evidence-based knowledge for safe midwifery practice as well as actively participate in research 68 . However, evidence-based practice and research are seen as a challenge for midwifery students 69 as well as practitioners 21 . A tension between evidence-based practice as well as research and practice is reported 69 .…”
Section: Master’s Programs In Midwiferymentioning
confidence: 99%
See 2 more Smart Citations
“…In its ‘International Code of Ethics for Midwives’, the ICM describes that midwives use up-to-date data and professional evidence-based knowledge for safe midwifery practice as well as actively participate in research 68 . However, evidence-based practice and research are seen as a challenge for midwifery students 69 as well as practitioners 21 . A tension between evidence-based practice as well as research and practice is reported 69 .…”
Section: Master’s Programs In Midwiferymentioning
confidence: 99%
“…However, evidence-based practice and research are seen as a challenge for midwifery students 69 as well as practitioners 21 . A tension between evidence-based practice as well as research and practice is reported 69 . Reasons for this include the lack of clinically active midwives with solid scientific training in many places have 67 and their lack of influence on the framework conditions and the control of these via management positions 8 .…”
Section: Master’s Programs In Midwiferymentioning
confidence: 99%
See 1 more Smart Citation